PERANAN KEPALA DESA DALAM MENGELOLA DANA DESA (Studi Kasus di Desa Gobo Kecamatan Simuk) - Matius Bangun; Fransiskus Pascal Bali (JURNAL GOVERNANCE OPINION, 2021)
This study aims to determine the performance of the Gobo Village Head in 2019 in managing the existing Village Fund. The main instrument used is the researcher himself because this research is a qualitative type. In addition, Village Fund management documents, cellphones, and interview sheets become additional instruments. Data were collected by documentation and interviews. The data that has been obtained is analyzed by adopting a reduction and data presentation stage which shows that the Gobo Village Head has carried out his role in accordance with the applicable rules. The results showed that the factors supporting the role of the Gobo Village Head in carrying out his role to manage the 2019 Village Fund were two internal factors (fixed income and village apparatus allowances, Village Government Operations, BPD Operations, Public Works and Spatial Planning, Settlement Areas), Energy and Mineral Resources Sector) and External Factors (Transfer Funds, District Government, Regency Government). The inhibiting factors for the role of the Gobo Village Head in carrying out his role to manage the 2019 Village Fund are internal factors (Village income sources, fixed income and allowances for the Village Head, Cultural and Religious Sector) and there are no external parties that hinder the role of the Village Head.